99mTc-FAPI-04 SPECT/CT outperforms contrast-enhanced CT in detecting metastasis in postoperative patients with colorectal cancer - Sun, Donghua; Ma, Li; Liu, Yan; Bao, Caili; Jia, Guorong; Wang, Tao; Wang, Yingqiu (Frontiers in Medicine, 2024)
Purpose: To compare the performance of 99m Tc-FAPI-04 SPECT/CT and contrast-enhanced CT (CECT) in the detection of postoperative metastasis in patients with colorectal cancer (CRC).The postoperative patients with CRC were consecutively recruited from January 2023 to June 2023, and the enrolled patients completed 99m Tc-FAPI-04 SPECT/CT imaging and CECT examination within two weeks. Histopathological analysis and the follow-up results were used as the reference criteria. The location and number of metastatic sites and the detection accuracy between the two imaging methods were compared. The tumor-to-background ratio (TBR) of liver metastasis and lymph node metastasis in 99m Tc-FAPI-04 SPECT/CT imaging were also calculated for comparison.In total, 19 postoperative CRC patients, including 15 patients with metastasis, were included in this study. In the patient-based analysis, 99m Tc-FAPI-04 SPECT/CT showed a significantly higher sensitivity for the detection of metastasis than CECT (93.3% vs. 80.0%, P = 0.038), but both techniques had the same specificity (100%, 4/4). For the lesion-based analysis, the detection rates of metastatic sites were 92.2% (47/51) and 72.5% (37/51) for 99m Tc-FAPI-04 SPECT/CT and CECT, respectively, and the difference between them was statistically significant. In the diagnosis of liver metastasis and lymph node metastasis, 99m Tc-FAPI-04 SPECT/CT both exceeded CECT. Additionally, the TBR in lymph node metastasis was higher than that in liver metastasis.The findings suggested that 99m Tc-FAPI-04 SPECT/CT could detect metastasis more effectively than CECT, especially liver and lymph node metastases, in postoperative CRC patients.